Perbandingan Regulasi Hak Cipta atas Video Parodi: Studi Kasus Pelanggaran di Indonesia dan Amerika Serikat - Arthaprima Devandra Julianto (Jurnal Hukum Lex Generalis, 2025)
The phenomenon of parody videos adapting copyrighted works (such as songs, films, and advertisements) has increased with the growth of digital technology and social media. In Indonesia, Law No. 28/2014 does not explicitly regulate fair use, creating legal uncertainty and leading to litigation-based dispute resolution. In contrast, the U.S., through the DMCA and U.S. Copyright Act, provides a clearer basis for fair use by applying four assessment factors: purpose, nature, amount, and economic impact. This normative and comparative legal study uses qualitative analysis to examine differences in copyright dispute mechanisms between the two countries, revealing significant contrasts in legal certainty and freedom of expression.